Aligning values and politics : empowerment versus entitlement - Gendre, Michael; Sánchez, Nicolás (Lanham, Maryland : University Press of America, 2016)
This book argues that politics must align with the promotion of self-actualization. Combining private property rights with an ethics of responsibility and drawing from the ideas of Immanuel Kant, the book opens the doors to a nonpartisan analysis of income inequality, inheritance, race relations, abortion and governance.
11 The Rise of Property Rights in Historical Context12 Bringing Back Legitimacy to Government; 13 Proposed Legal and Constitutional Changes; 14 The Obstacles That We Still Face; 15 The Road to Wealth Creation in a Society with Meaningful Lives; 16 Imperialism as a Threat to American Governance; 17 From Ancients to Moderns; Afterword and Summary in the Form of an Open Letter; Appendix A; Appendix B; Appendix C; Bibliography; Index; About the Authors
Includes bibliographical references (pages 159-161) and index.
Print version record and CIP data provided by publisher; resource not viewed.
eBooks on EBSCOhost
Keywords: Ethics -- Political aspects -- United States; Political ethics -- United States; United States -- Politics and government; Political participation -- United States; Transparency (Ethics) in government -- United States; Political culture -- United States; Social change -- United States; Morale -- Aspect politique -- États-Unis.; Morale politique -- États-Unis.; États-Unis -- Politique et gouvernement; Participation politique -- États-Unis.; POLITICAL SCIENCE -- Essays; POLITICAL SCIENCE -- Government -- General; POLITICAL SCIENCE -- Government -- National; POLITICAL SCIENCE -- Reference; Political ethics; Political culture; Political participation; Politics and government; Social change; Transparency in government; United States; Electronic book